SESEMAT Pedagogical Approaches and Physics Teacher Effectiveness in Kigezi Sub-Region, Uganda - Tukamuhabwa,Evaristo; Kishabale, Bashir; Lubaale, Grace (Journal of Research in Education and Technology, 2024)
Effective physics teachers in secondary schools in Kigezi Sub-Region are a focus to improve the scientific skills, competences and students’ academic knowledge to the required content. There are however, increasing concerns among stake holders about teacher ineffectiveness which has caused dismal performance of students in science subjects particularly physics. The study investigated the influence of Secondary Science and Mathematics Teachers (SESEMAT) pedagogical approaches on physics teacher effectiveness in secondary schools in Kigezi Sub Region, Uganda. Guided by Cognitive Constructivist theory, the study adopts a perspective that views learning as an active process, where contexts of learners are fully considered and learners being motivated and then collaborative learning takes place. Out of a population of 620, a sample of 234 Physics teachers was drawn from secondary schools of Kigezi Sub- Region. Data collection tool comprised of a questionnaire. Collected data was analysed descriptively using statistical software programs SPSS and SPSS AMOS. The findings showed that physics teacher effectiveness is highly influenced by SESEMAT pedagogical approaches in all aspects. The analysis results of structural equation model (SEM)/path analysis showed that SESEMAT pedagogical approaches influenced teacher effectiveness. Hence the causal relationship between SESEMAT pedagogical approaches and teacher effectiveness was positive and significant. The tested hypotheses state that there is a significant influence of SESEMAT pedagogical approaches on physics teacher effectiveness. It was concluded that SESEMAT Pedagogical approaches (active learning, motivation of students, contextual learning, and collaborative learning) are important to physics teacher effectiveness. Therefore, it was recommended that Physics teachers in Kigezi Sub-Region should apply SESEMAT pedagogical approaches while teaching in a good environment for better performance of learners and skills acquisition.